2004
DOI: 10.1287/orsc.1040.0074
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Contract: Evidence from the Personal Computer Industry

Abstract: O rganizational forms involving more detailed contracts than are found in traditional spot market exchanges appear to be increasingly prevalent. There has been relatively little analysis, however, of the extent to which firms learn how to use contracts to manage their interfirm relationships over time. In this paper, we conduct a detailed case study of a time series of 11 contracts concluded during 1989-1997 between the same two partners, both of whom participate in the personal computer industry, to explore w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
791
3
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 769 publications
(850 citation statements)
references
References 55 publications
47
791
3
9
Order By: Relevance
“…As we noted in our description of the structural school of thought on inter-organizational coordination, joint-venture structures can facilitate coordination by providing robust authority structures and enforcement mechanisms, dedicated staff, and opportunities to devise structures and procedures that fit the purpose of the alliance (Gulati & Singh, 1998). Detailed contracts can help address coordination challenges (Mellewigt et al, 2007;Reuer & Arino, 2007) by specifying tasks, roles, and responsibilities (Carson et al, 2006;Mayer & Argyres, 2004); contingency plans and responses (Ring & Van de Ven, 1994), and information-sharing and feedback channels to ensure smooth operation. Forwardlooking firms are likely to weigh those benefits against the higher costs of both JVs and detailed contracts and to select more formal governance when their coordination needs are highest, such as in situations characterized by high task uncertainty and interdependence (Gulati & Singh, 1998;Mesquita & Brush, 2008), incompatibilities stemming from partner diversity (White, 2005), or high costs for coordination failure (Mellewigt et al, 2007).…”
Section: Alliance Designmentioning
confidence: 99%
See 1 more Smart Citation
“…As we noted in our description of the structural school of thought on inter-organizational coordination, joint-venture structures can facilitate coordination by providing robust authority structures and enforcement mechanisms, dedicated staff, and opportunities to devise structures and procedures that fit the purpose of the alliance (Gulati & Singh, 1998). Detailed contracts can help address coordination challenges (Mellewigt et al, 2007;Reuer & Arino, 2007) by specifying tasks, roles, and responsibilities (Carson et al, 2006;Mayer & Argyres, 2004); contingency plans and responses (Ring & Van de Ven, 1994), and information-sharing and feedback channels to ensure smooth operation. Forwardlooking firms are likely to weigh those benefits against the higher costs of both JVs and detailed contracts and to select more formal governance when their coordination needs are highest, such as in situations characterized by high task uncertainty and interdependence (Gulati & Singh, 1998;Mesquita & Brush, 2008), incompatibilities stemming from partner diversity (White, 2005), or high costs for coordination failure (Mellewigt et al, 2007).…”
Section: Alliance Designmentioning
confidence: 99%
“…Some of the mechanism for coordination that partners develop over time can become routines that are implemented informally (Reuer & Arino, 2007), but some will be formalized in contracts that effectively serve as -repositories of knowledge‖ distilling the lessons of past coordination failures Argyres, Bercovitz, & Mayer, 2007). For example, partners' experiences of misunderstandings resulting from poor informal communication in prior alliances may prompt them to formalize information-exchange provisions in their subsequent alliance contracts (Mayer & Argyres, 2004). 18 Such experiential learning also occurs in the design of cooperation-related contractual clauses.…”
Section: Alliance Designmentioning
confidence: 99%
“…It is likely that certain types of concerns are best addressed through formal protection whereas others require social mechanisms to be invoked. While contracts and courts are a valid deterrent to opportunistic behavior, scholars have shown that these are in reality rarely invoked explicitly (Eccles 1981;Mayer and Argyres 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Diversos autores han mostrado intentos de materializar esa relación. Estos autores han abordado diferentes aspectos de esta relación, entre ellos, la confianza (Dyer, 1997;Poppo & Zenger, 2002), la coordinación eficiente (Langlois & Foss, 1999), la creación de mayores beneficios en la firma (Madhok, 1996), el aprendizaje (Mayer & Argyres, 2004), la mejora de la capacidad de elección (Hoetker, 2005), la reducción de costos de transacción bajo riesgos contractuales (Mayer & Salomon, 2006) y el complemento para la innovación . Este nuevo constructo se conoce, en la literatura, como la capacidad transaccional y será ampliado en el próximo ítem.…”
Section: Capacidad Transaccional: Una Perspectiva Integradoraunclassified